ANALISIS KADAR MERKURI (Hg) SEBAGAI DAMPAK KEGIATAN PENAMBANGAN EMAS DI BATANG AIR CARACAI NAGARI GANGGO HILIA KECAMATAN BONJOL KABUPATEN PASAMAN - Muhammad Alfindo; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine and analyze levels of mercury (Hg) and its distribution in Batang Air Caracai Nagari Ganggo Hilia. In conducting a class analysis of mercury content (Hg) the researcher used Government Regulation No. 82 of 2001 as a reference for determining the grade level. Determination of the class distribution of mercury levels in Batang Air Caracai can use the Interpolation method with the Inverse Distance Weight Method in ArcGis and sampling is carried out at 11 location points which are spread from upstream to downstream and river water samples are then analyzed in the laboratory. The mercury content values ​​at the 11 points were 0.392mg / L, 0.415mg / L, 0.431 mg / L, 0.438 mg / L, 0.507 mg / L, 0.484 mg / L, 0.323 mg / L, 0.23 mg / L, respectively. L, 0.461 mg / L, 0.533 mg / L and 0.806 mg / L. Based on research that has been carried out by mercury (Hg) contamination on Batang Air Caracai shows that it exceeds class IV in PP No. 82 of 2001 which means that this Caracai Air Rod cannot be used according to its designation such as, toilets, agriculture, livestock and others. The distribution of mercury (Hg) levels in Batang Caracai shows that the lower the levels of mercury (Hg) are.